Quality of life of Older Persons During the Second Wave of the COVID-19 Pandemic in Thailand - Waelveerakup, Wanpen; Suwannasarn, Korawan; Pasuwan, Duangporn (Journal of The Royal Thai Army Nurses, 2023)
This research aimed to study 1) the quality of life of older persons during the second wave of the coronavirus disease 2019 outbreak and 2) compare the quality of life of older persons during the second wave of the coronavirus disease 2019 outbreak classified by age, gender, marital status, congenital disease, number of family members economic status and the need for social support. A descriptive study was adopted. The 267 older persons were selected by multi-stage sampling. The personal characteristics questionnaire, the Social Support Needs Questionnaire (SSNQ), and the WHO Quality of Life Questionnaire, the Thai version (WHOQOL – BREF – THAI), were used to collect the data. Data were analyzed using descriptive statistics, one-way ANOVA, and an independent t-test. The results found that the older persons had a moderate overall quality of life (M = 81.5, SD = 6.8) and that mental quality of life was at a poor level (13.90%). Older persons of different ages had the different quality of life. However, gender, congenital disease, family economic status, marital status, number of family members, and the need for social support did not affect the quality of life differences. In conclusion, older persons had a moderate quality of life. Therefore, it should promote the quality of life, especially for those aged 80 and over. Activities to promote the quality of life during the outbreak of COVID-19 should focus on activities that promote the quality of life in terms of mental status.